2020
DOI: 10.1007/s12013-020-00906-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Curcumin on Lipid Membranes: an EPR Spin-label Study

Abstract: Curcumin is a yellow–orange dye widely used as a spice, food coloring and food preservative. It also exhibits a broad range of therapeutic effects against different disorders such as cancer, diabetes, or neurodegenerative diseases. As a compound insoluble in water curcumin accumulates in cell membranes and due to this location it may indirectly lead to the observed effects by structurally altering the membrane environment. To exert strong structural effects on membrane curcumin needs to adopt a transbilayer or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 41 publications
3
21
1
Order By: Relevance
“…Meanwhile, it has also been shown that the protein function is regulated by the properties of the lipid bilayer as a result of the hydrophobic coupling between the protein and the core of the bilayer . These assertions have motivated investigations of the interaction mechanism between curcumin and lipid bilayers. , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, it has also been shown that the protein function is regulated by the properties of the lipid bilayer as a result of the hydrophobic coupling between the protein and the core of the bilayer . These assertions have motivated investigations of the interaction mechanism between curcumin and lipid bilayers. , …”
Section: Introductionmentioning
confidence: 99%
“…Various experimental methods including X-ray diffraction, resonance spectroscopy, and calorimetry have been used to understand the interaction between curcumin and PC lipid bilayers. Curcumin is a predominantly hydrophobic molecule (Figure ) , that shows a high affinity toward PC membranes. The interaction between curcumin and PC membranes is exothermic and a large partition coefficient (∼10 6 ) is observed. ,, But the position and orientations of curcumin in PC membranes are controversial. Two different positions of curcumin (i) at the membrane interface, specifically between the membrane head and tail, with its long axis parallel to the plane of the membrane (referred to as surface-associated orientation) and (ii) deeply inserted in the hydrophobic core of the bilayer with its long axis perpendicular to the plane of membrane or transbilayer orientation have been observed. For example, using nuclear magnetic resonance (NMR) spectroscopy, Barry et al concluded that curcumin has transbilayer orientation in the dimyristoylphosphatidylcholine (DMPC) membrane even at low concentrations. However, using X-ray lamellar diffraction, Huang and co-workers revealed that at low molar concentrations (<3 mol %), curcumin binds at the interface of the 1,2-dioleoyl- sn -glycero-3-phosphocholine (DOPC) membrane, sitting between the head and the tail, with its long axis parallel to the plane of the membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher values of 2Azz indicate higher polarity (lower hydrophobicity) and polarity profiles across the lipid bilayer reflect water penetration into the membrane [ 95 ]. This can be affected by lipid composition, presence of cholesterol, carotenoids, peptides, or drugs [ 94 , 96 , 97 , 98 , 99 ]. Here, we analyzed the effect of TUDCA on polarity profiles across two simple models of membranes containing high and low level of cholesterol ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Usually, carotenoids are located inside cell membranes as highly lipophilic molecules. While strict hydrocarbons, such as lycopene or β-carotene, are arranged exclusively in the inner part of the lipid bilayer, molecules with a more polar configuration containing oxygen atoms attached (like lutein or zeaxanthin) are oriented roughly perpendicular to the membrane surface with their hydrophilic parts oriented to the aqueous environment [ 29 , 30 ].…”
Section: Natural Antioxidantsmentioning
confidence: 99%